Comparative evaluation of polymethylmethacrylate and composite bone cements. Review of the experimental studies results - Vyrva, Oleg; Goncharuk, Olexii; Lysenko, Natalia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Current article is a review of experimental studies of different bone cements types and their combinations. Providing of bone fragments stable fixation at osteosynthesis in cases of difficult multifragmental fractures, arthroplasties and other implants using especially in the osteoporosis conditions is a main task of orthopaedic surgery procedures. Polymethylmethacrylate (PMMA) is the first material that is answered to these requirements. The evolution of bone cements resulted in creation of a new composite substance — combination of PMMA and β-threecalciumphosfates (β-TCPh). Combination of these two components allowed to provide high bioabsorbal, osteoconductive and osteointegrative properties along with sufficient durability. In the analyzed works the properties of composite cement CalCemex were evaluated in vivo experiment. It was found that in the case of PMMA penetration of bone tissue into the polymer structure did not occur. Under the conditions of using bone cement with β-TCF admixture, the formation of bone tissue was observed not only on the surface of the implant, but also in the external and internal pores. It is the presence of pores in CalCemex that the authors explain the possibility of penetration of cellular elements, blood vessels and bone formation. Moreover, β-TCPh is included into this material and it is bioresorbed by osteoclasts. This leads to the release of calcium and phosphorus ions and, consequently, simplifies the attachment of the newly formed bone to the bone cement. We assume that composite cement like CalCemex type is a promising material for the treatment of various types of fractures and replacement of bone defects. It should be mentioned that research in this area is ongoing and intensive work is underway to synthesize and study the results of clinical application of composite bone cements with maximum bioactive properties that will not only strengthen bone tissue but also perform osteointegrative function. Key words. Bone cement, polymethylmethacrylate, β-threecalciumphosfates, experiment.